The impact of the strategy of electronic mental maps on the development of mind habits The students of the Department have the teacher of the first grades in educational psychology - Jamal Khasif Al-Alawi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The aim of the current research is to identify the impact of electronic mental maps strategy on developing habits of mind among students of the first grades teacher’s department in the subject of educational psychology. (40) male and female students in the experimental group and (40) male and female students in the control group. The experiment was conducted during the second semester of the academic year (2022-2023), as the beginning of the actual teaching was on Sunday 26/2/2023 and its end on Sunday 11 / 5/ 2023 In order to achieve the goal of the research, the researcher adopted a scale (Al-Sayed et al., 2015) to measure habits and to ensure the validity and stability of the tool. It was presented to a few experts specialized in teaching methods, measurement, evaluation and psychology. The habits of mind scale was applied to the experimental and control groups on Sunday corresponding to (5/14/2023(